2020
DOI: 10.1002/jcp.29261
|View full text |Cite
|
Sign up to set email alerts
|

PSMC6 promotes osteoblast apoptosis through inhibiting PI3K/AKT signaling pathway activation in ovariectomy‐induced osteoporosis mouse model

Abstract: There is now increasing evidence which suggests a key role for osteoblast apoptosis in the pathogenesis of postmenopausal osteoporosis. Here, we evaluated the role and mechanism of proteasome 26S subunit, ATPase (PSMC) 6, a protein that is highly expressed in bone. Gene expression pattern had been extracted based on database of Gene Expression Omnibus (GEO). GEO2R was employed for analyses, while the DAVID database was adopted to further analyze the gene ontology (GO) as well as Kyoto Encyclopedia of Genomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Here, it should be emphasized that apoptosis of osteoblasts was also shown to be directly induced under some pathological agents, such as hypoxia 164 , Es deficiency 165 , aging 166 , and GCs 167 , etc, which enhanced the reduction of the number of osteocyte processes, eventually leading to increased bone resorption and decreased BMD. However, autophagy or apoptosis of osteocytes, as the most abundant cells in bone, could have a more important role in osteoclastogenesis-triggered bone loss, compared with apoptosis of osteoblasts.…”
Section: The Role Of Apoptotic Osteocytes In Osteoclastogenesis-triggmentioning
confidence: 99%
“…Here, it should be emphasized that apoptosis of osteoblasts was also shown to be directly induced under some pathological agents, such as hypoxia 164 , Es deficiency 165 , aging 166 , and GCs 167 , etc, which enhanced the reduction of the number of osteocyte processes, eventually leading to increased bone resorption and decreased BMD. However, autophagy or apoptosis of osteocytes, as the most abundant cells in bone, could have a more important role in osteoclastogenesis-triggered bone loss, compared with apoptosis of osteoblasts.…”
Section: The Role Of Apoptotic Osteocytes In Osteoclastogenesis-triggmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway plays an important role in regulating proliferation, osteoblast differentiation and osteoclast differentiation, apoptosis ( Zhang et al, 2020 ; Ye et al, 2019 ). Studies have shown that GLP-1RA can regulate PI3K/AKT signaling pathway through GLP-1R to alleviate cell apoptosis ( Xie et al, 2018 ; Ming-Yan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…PSMC6 belongs to PSMC family members [17]. PSMC6 might be candidate biomarkers associated with apoptosis in Melanosis coli and osteoblast [18,17]. AURKB plays a key role during mitosis [19].The role of the AURKB expression in cancer prognosis is controversial.…”
Section: Discussionmentioning
confidence: 99%